Incentivizing Organ Donation Under Different Priority Rules: The Role of Information - Li, Mengling; Riyanto, Yohanes E. (Management Science, 2025)
This paper examines the incentive to register for deceased organ donation under alternative organ allocation priority rules, which may prioritize registered donors and/or patients with higher valuations for organ transplantation. Specifically, the donor priority rule grants higher priority on the organ waiting list to those who have previously registered as donors. The dual-incentive priority rules allocate organs based on donor status, followed by individual valuations within the same donor status, or vice versa. Both theoretical and experimental results suggest that the efficacy of the donor priority rule and the dual-incentive priority rules critically depends on the information environment. When organ transplantation valuations are unobservable prior to making donation decisions, the hybrid dual-incentive rules generate higher donation rates. In contrast, if valuations are observable, the dual-incentive priority rules create unbalanced incentives between high- and low-value agents, potentially undermining the efficacy of the hybrid dual-incentive rules in increasing overall donation rates. This paper was accepted by Marie Claire Villeval, behavioral economics and decision analysis. Funding: This research is supported by the National Natural Science Foundation of China [Grants 72173103, 72373127, and 71988101], the Singapore Ministry of Education (MOE) Academic Research Fund Tier 1 [RG57/20], and the Open Foundation of Key Laboratory of Interdisciplinary Research of Computation and Economics (Shanghai University of Finance and Economics), Ministry of Education of China. Supplemental Material: The online appendices and data files are available at https://doi.org/10.1287/mnsc.2022.01530 .